O princípio da insignificância à luz da jurisprudência do Supremo Tribunal Federal - Melloni, Amanda (2024)
The principle of insignificance serves as a vital tool for achieving justice, as it upholds a penal system that is fair, proportional, and ethical. While it is widely accepted in legal doctrine and jurisprudence, uncertainties still linger regarding the application of the theory of insignificance in Brazilian criminal law, primarily due to the lack of clearly defined parameters for its implementation. This study aims to analyze the factors established in the decisions of the Supreme Federal Court concerning the principle of insignificance, including the jurisprudential evolution of the principle itself, which encompasses both objective and subjective criteria. The inclusion of these criteria has led to doctrinal and jurisprudential divergences. By presenting rulings from the Supreme Court that illustrate the application of the principle of insignificance, a critical analysis of the topic will be conducted, aiming to contribute to a discussion that fosters a more humane, reasonable criminal law that embraces t